2020
DOI: 10.3390/biom10081188
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans Models to Study the Propagation of Prions and Prion-Like Proteins

Abstract: A hallmark common to many age-related neurodegenerative diseases, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS), is that patients develop proteinaceous deposits in their central nervous system (CNS). The progressive spreading of these inclusions from initially affected sites to interconnected brain areas is reminiscent of the behavior of bona fide prions in transmissible spongiform encephalopathies (TSEs), hence the term prion-like proteins has been coined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 173 publications
(203 reference statements)
0
4
0
Order By: Relevance
“…We used C. elegans as a versatile in vivo model to evaluate the toxicity of R3Ags with or without drug treatment [35,36]. Drug-capped and drug-preinhibited R3Ags were administered to worms for 2 h, and the pharyngeal pumping was scored after an additional 2-24 h to determine whether the drug treatment affected aggregate-mediated toxicity in vivo (Fig.…”
Section: Drugs Protect C Elegans From R3ags-mediated Toxicitymentioning
confidence: 99%
“…We used C. elegans as a versatile in vivo model to evaluate the toxicity of R3Ags with or without drug treatment [35,36]. Drug-capped and drug-preinhibited R3Ags were administered to worms for 2 h, and the pharyngeal pumping was scored after an additional 2-24 h to determine whether the drug treatment affected aggregate-mediated toxicity in vivo (Fig.…”
Section: Drugs Protect C Elegans From R3ags-mediated Toxicitymentioning
confidence: 99%
“…It is currently understood that the neurodegenerative disease-related proteins, especially TDP-43 (ALS), amyloid beta and tau (Alzheimer's disease), α-synuclein (Parkinson's disease, PD), and FUS (frontotemporal dementia, FTD), partially show some characteristics of misfolding prion proteins. In addition, the TDP-43 C. elegans model also showed that the autophagy-lysosome pathway is the prion-like transmission pathway of TDP-43 protein (Sandhof et al, 2020 ). Meanwhile, it was discovered that the regulation of autophagy or exocytosis/endocytosis can affect the transfer of these misfolded proteins (Tyson et al, 2017 ).…”
Section: C Elegans Modelsmentioning
confidence: 99%
“…The nematode worm, Caenorhabditis elegans ( C. elegans ), provides an excellent model system for understanding underlying disease biology in neurodegenerative conditions [ 20 , 27 , 28 ] and is a promising candidate for functional dissection of the complex genetic architecture of PD. Between 60-80% of human genes have orthologues in C. elegans [ 29 ] and its genome was the first of any multicellular organism to be completely sequenced [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%